Identifying the key regulators orchestrating Epstein-Barr virus reactivation - Wang, Yaohao; Yu, Jingwen; Pei, Yonggang (Frontiers in Microbiology, 2024)
Epstein-Barr virus (EBV) infects more than 90% of the human population worldwide and establishes lifelong infection in hosts by switching between latent and lytic infection. EBV latency can be reactivated under appropriate conditions, leading to expression of the viral lytic genes and production of infectious progeny viruses. EBV reactivation involves crosstalk between various factors and signaling pathways, and the subsequent complicated virus-host interplays determine whether EBV continues to propagate. However, the detailed mechanisms underlying these processes remain unclear. In this review, we summarize the critical factors regulating EBV reactivation and the associated mechanisms. This encompasses the transcription and post-transcriptional regulation of immediate-early (IE) genes, the functions of viral factors on viral DNA replication and progeny virus production, the mechanisms through which viral proteins disrupt and inhibit the host’s innate immune response, and the host factors that modulate EBV reactivation. Finally, we explore the potential applications of novel technologies in studying EBV reactivation, providing novel insights into the investigation of mechanisms governing EBV reactivation and the development of anti-EBV therapeutic strategies.